A synergistic therapy against influenza virus A/H1N1/PR8 by a HA1 specific neutralizing single-domain VL and an RNA hydrolyzing scFv - Hoang, Phuong Thi; Luong, Quynh Xuan Thi; Ayun, Ramadhani Qurrota; Lee, Yongjun; Oh, Kwang-Ji; Kim, Taehyun; Lee, Taek-Kyun; Lee, Sukchan (Frontiers in Microbiology, 2024)
The emergence of anti-influenza drug-resistant strains poses a challenge for influenza therapy due to mutations in the virus's surface protein. Recently, there has been increasing interest in combination therapy consisting of two or more drugs as a potential alternative approach, aiming to enhance therapeutic efficacy. In this study, we investigated a novel synergistic therapy with a vertical effect using a single-domain VL -HA1 specific antibody against H1N1/PR8 and a horizontal effect using an RNA catalytic antibody with broad-spectrum influenza antiviral drug. We isolated a single-domain VL -HA1 specific (NVLH8) antibody binding to the virus particles showing a neutralizing activity against influenza virus A, H1N1/PR8 specifically, as determined by the reduction of plaque number and lower viral HA protein expression in vitro. The neutralizing antibody likely prevented the viral entry, specifically at the viral genome-releasing step. Additionally, the 3D8 scFv hydrolyzed viral RNAs in the cytoplasm, including mRNA, vRNA, and cRNA in MDCK cells. The combined treatment of neutralizing antibodies for a vertical effect and 3D8 scFv for a horizontal effect produced a synergistic effect providing a novel approach against viral disease when compared to a single treatment. Our results indicated that combining treatment, in particular, two proteins exhibiting different mechanisms of action increased the antiviral activity against the influenza virus.